2015
DOI: 10.1097/md.0000000000001653
|View full text |Cite
|
Sign up to set email alerts
|

Predicting of Venous Thromboembolism for Patients Undergoing Gynecological Surgery

Abstract: The purpose of this study was to determine the risk stratification of deep venous thrombosis (DVT) in patients undergoing gynecological surgery.A retrospective study was conducted with a cohort of 739 consecutive female patients undergoing gynecological surgery between May 2008 and July 2013 in Beijing Chao-yang hospital. DVT of the leg was detected using complete compression and color Doppler ultrasound. Pulmonary embolism (PE) was diagnosed by computed tomography pulmonary angiogram (CTPA).The overall incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 28 publications
(34 reference statements)
0
36
0
2
Order By: Relevance
“…3 Although high body mass index (930 kg/m 2 ) is generally considered a risk factor for development of VTE, small studies specifically looking at patients with gynecological malignancy have not been able to demonstrate it to be a significant risk factor. 9 Specific tumor factors including type, size, and stage were also implicated in the risk profile. Considering cervical cancer, tumors of greater than 50 mm increased the risk of VTE by almost 9 times (10.2% 950 mm vs 1.2% G50 mm,) as did being Federation of Gynecology and Obstetrics stage IV (27.8% stage IV vs 3.2% stages I-III.)…”
Section: Etiology/risk Factorsmentioning
confidence: 99%
“…3 Although high body mass index (930 kg/m 2 ) is generally considered a risk factor for development of VTE, small studies specifically looking at patients with gynecological malignancy have not been able to demonstrate it to be a significant risk factor. 9 Specific tumor factors including type, size, and stage were also implicated in the risk profile. Considering cervical cancer, tumors of greater than 50 mm increased the risk of VTE by almost 9 times (10.2% 950 mm vs 1.2% G50 mm,) as did being Federation of Gynecology and Obstetrics stage IV (27.8% stage IV vs 3.2% stages I-III.)…”
Section: Etiology/risk Factorsmentioning
confidence: 99%
“…Conversely, a study of 739 patients undergoing gynecological surgery in Beijing, China, found that around 97% of DVT were diagnosed within 1 week of surgery. As early VTE (days 0–7) is thought to be surgery related, while late VTE (days 8–90) reflects the recovery period, the authors concluded that the first week after surgery is an important period for VTE detection . All of our women had clinic follow‐up at least 6 weeks postoperation and none of them reported any symptoms of VTE.…”
Section: Discussionmentioning
confidence: 79%
“…Studies on women undergoing gynecological surgery found that independent risk factors for VTE include prior VTE, varicose veins, increasing age, gynecological malignancy and prior radiotherapy . Perioperative factors such as laparotomy approach, prolonged surgery (>3 h), transfusion and bed rest (>48 h) were significantly associated with VTE .…”
Section: Discussionmentioning
confidence: 96%
“…VTE risk stratification was performed according to the 2008 American College of Chest Physicians guidelines on VTE prevention 1 and our previous studies on risk factors for VTE 4 , 18 . Risk factors analyzed included age ≥50 years, hypertension, previous DVT/PE, thrombophilia, previous cerebral infarction, previous myocardial infarction, lower extremity varices, present surgery for malignancy, laparotomy surgery, operative time ≥3 h, and postoperative bed rest time ≥48 h. Patients with ≤2 risk factors but ≥1 risk factor were deemed to have a moderate level of risk for DVT, those with 3 risk factors deemed to have a high level, and those with ≥4 factors deemed to have a very high level.…”
Section: Methodsmentioning
confidence: 99%
“…Venous thromboembolism (VTE), manifesting mainly as deep venous thrombosis (DVT) and pulmonary embolism (PE), is a common serious complication of gynecologic surgery 1 . Epidemiological studies from our team and other groups show that the incidence of DVT following gynecologic surgery ranges from 6.2% to 37.9% 2 4 . Although the true incidence of PE in patients after gynecologic surgery is currently unknown, it has been reported that 0.3–4.4% of patients undergoing thromboembolic prophylaxis after gynecologic oncology surgery developed PE 5 , 6 .…”
Section: Introductionmentioning
confidence: 91%